Analisis Profil Lulusan Program Studi Teknik Industri Berdasarkan Kebutuhan Pasar Kerja - Yohanes Dicka Pratama; Kristoforus Jawa Bendi; Suzzana Winda Artha Mustika (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2018)
The purpose of this study is to find out the profile of college graduates currently required by the labor market. The graduate profile to be analyzed is the graduate profile of the field of industrial engineering based on the needs of the labor market. In addition to getting an overview of the graduate profile, this study also wants to analyze the capabilities that the industrial engineering graduate must have with regard to the profile of the identified graduates. To analyze the ability of graduates, then used K-DIKTI (Higher Education Curriculum) as a reference, that is related to; attitudes or values, general ability, special abilities, and knowledge. To identify the profile of graduates and the capabilities that must be possessed, in this study using job advertisements that are online. The analytical method used is descriptive analysis method. This method is used because it can help in arranging the data obtained from job advertisements, so that data can describe the meaningful information. The results of this study are expected to provide additional information for the study program when going to do recuriculla. From the results of data collection there are several graduate profiles for industrial engineering study programs. Of the several profiles needed, the most needed is as an engineer, which is around 27.27%, then the second is PPIC, around 21.21%.